Riedel’s Thyroiditis: Misdiagnosed Case on Fine Needle Aspiration Cytology- a lesson to learn! - Hashmi, Mubashira; Sanaullah Gazozai, Sanaullah Gazoza (International Journal of Pathology, 2018)
Reidel’s thyroiditis is a rare form of chronic thyroiditis, in which fibro inflammatory process destroysthe thyroid partially or completely. It involves the surrounding tissue like skeletal muscles, vessels, trachea,esophagus and upper mediastinum. These “infiltrative features” compounded with some inflammatory atypia maylead to mistaken diagnosis of malignancy! Here we describe such a misdiagnosed case. Final diagnosis of Reidel’sthyroiditis was made on histopathological examination of the sub-total thyroidectomy specimen. We suggest that ifa patient is presenting with the features of thyroid malignancy, Reidel’s thyroiditis should be keep in mind as adifferential diagnosis.